Eksistensi Pacu Jalur Tradisional di Desa Sungai Pinang Kabupaten Kuantan Singingi Provinsi Riau (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
There is growing concern over the fading of local cultural traditions due to the influence of globalization; therefore, a scientific study is needed to understand the functions, meanings, and roles of the Pacu Jalur tradition in community life. This research aims to examine the existence of the Pacu Jalur tradition in Sungai Pinang Village as a form of local cultural heritage that continues to survive amid modernization and social change. The study employs a qualitative approach using interviews, observations, and documentation to obtain in-depth data from various informants. The findings indicate that Pacu Jalur has multidimensional functions, including ritual, entertainment, moral education, economic, as well as identity and social integration functions. This tradition not only strengthens social solidarity and cohesion within the community but also contributes to character building among the younger generation and enhances the local economy through cultural tourism. In conclusion, the Pacu Jalur tradition in Sungai Pinang Village remains strong and relevant, and therefore needs to be preserved sustainably through the support of both the community and the government so that it continues to live on and retain its significance for future generations.